Efficacy and safety of nab-paclitaxel plus platinum in non-small cell lung cancer: a meta-analysis - Tan, Tianying; Li, Shuangshuang; Hu, Wenting; Yue, Tinghui; Zeng, Qi; Zeng, Xingling; Chen, Xiaochao; Zhao, Xiangdong; Xiao, Tianbao (Frontiers in Medicine, 2023)
Purpose This meta-analysis was exerted in assessing the anticancer efficacy and safety of nab-paclitaxel (nab-P) when combined with platinum compound agents for therapy in patients with non-small cell lung cancer (NSCLC). Method We systematically searched the following seven electronic databases: PubMed, Cochrane Library, Web of Science, Embase, CNKI, Wan Fang, and China Science and Technology Journal Data. Randomized comparative clinical [randomized controlled clinical trial (RCT)] studies on nab-P plus platinum and carboplatin or cisplatin in combination with conventional chemotherapy agents or traditional paclitaxel were searched. Results A total of 19 RCT studies involving 6,011 patients were analyzed. The primary outcome includes the overall response rate (ORR), overall survival (OS), and progression-free survival (PFS). The secondary outcome includes adverse events (AEs). Nab-P combined with platinum (carboplatin/cisplatin) had a better ORR [odds ratio (OR) = 1.66, 95% confidence interval (CI) (1.34, 2.05), p < 0.001] and improved PFS [hazard ratio (HR) = 0.84, 95% CI: (0.74, 0.94), p = 0.01] and OS [HR = 0.86, 95% CI: (0.78, 0.96), p = 0.008] in NSCLC patients. ORR [OR = 2.18, 95% CI: (1.07, 4.43)], PFS [HR = 0.62, 95% CI: (0.40, 0.97)], and OS [HR = 0.63, 95% CI: (0.49, 0.81)] were significantly improved among patients aged >70 years, and ORR [OR = 1.80, 95% CI: (1.20, 2.70)] and PFS [HR = 0.74, 95% CI: (0.56, 0.97)] were significantly elevated with SCC rate ≥65% in NSCLC patients (all p > 0.05). Among the adverse effects, the prevalence of neutropenia, neuralgia, and arthralgia/myalgia (≥ grade 3) compared to that of the control group. On the other hand, the prevalence of anemia and thrombocytopenia was higher in the nab-P plus platinum (carboplatin/cisplatin) compared to that of controls. It is worth noting that fatigue did not show statistical significance. Conclusion Nab-P in combination with carboplatin/cisplatin regimen improves efficacy and tolerability in patients with NSCLC. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022288499.